The Underground Railroad and the politics of narration in Harriet Beecher Stowe’s Uncle Tom’s Cabin (1852) - Delphine Louis-Dimitrov (Revue LISA)
This article examines the literary politics underlying the Underground Railroad plotline in Harriet Beecher Stowe’s Uncle Tom’s Cabin (1852). It highlights the structuring function of philosophical and political principles drawn from romantic reform and transcendentalism, showing how they articulate with distinct literary strategies to convey an antislavery discourse targeting the 1850 Fugitive Slave Law. While the plotline is governed by a chain of sympathy relying on a reinterpretation of the antislavery principle of moral suasion, notably embraced by William Lloyd Garrison in the 1830s, the characterization of the enslaved fugitives as heroic rebels emphasizes the necessity of active and martial resistance to bondage, a strategy which gained prominence among abolitionists in the 1850s. The Underground Railroad ultimately serves as a narrative conduit for a democratic reconfiguration of history that lends voice, visibility and political agency to enslaved fugitives. The novel’s indictment of pro-slavery laws thereby opens onto a call for the regrounding of American democracy on the principle of higher law.